RETRACTED: About some of Osman Kochqor’s translations In Uzar literature - Norova Nasiba; Davronova Shokhsanam; Axmedova Shoira; Xudoyqulova Marhabo (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001